Rancang Bangun Sistem Pengering Ikan Berbasis ESP32 dan Sensor Suhu-Kelembaban untuk Teknologi Tepat Guna Masyarakat Pesisir - Ditya Zul Asmi; Silvy Windha Mediaswari; Ihsanulfu’ad Suwandi (Politeknik Kebangsaan, 2025)
This researched aimed to design and develop a low cost fish drying system using ESP32 integrated with temperature and humidity sensors as an appropriate technology solution for coastal communities. Traditional fish drying methods still rely on sunlight exposure, which is highly influenced by weather, produces inconsistent moisture levels, and increases the risk of contamination and microbial growth. To address these issues, this study proposes an Internet of Things (IoT) based controlled drying system capable of maintaining optimal temperature and humidity levels. The ESP32 microcontroller is utilized to collect sensor data in real time, control the heating element and ventilation system, and transmit drying information to a monitoring dashboard via Wi-Fi and a local OLED display. The results show that the proposed system can reduce drying duration and improve fish quality compared to traditional techniques, making it suitable as an appropriate technology for coastal communities.